The Role of Virus Vectors in Orange Fleshed Sweetpotato Genotypes Infection - A Case Study (Global Journal of Science Frontier Research, 2015)
The economic importance of sweetpotato as a carbohydrate food and feed for man and animals is well known in the world all over. Sweetpotatoes are crops vegetatively propagated from vines, root slips (sprouts), and farmers often take vines for propagation from their own field year after year. Therefore, virus diseases are inevitably transmitted with propagation materials to newly planted field, resulting often in a marked decrease in yield. A virus infection is often spread by insects that pierce and suck. As is the case, no living organism such as sweetpotato is absolutely virus-free in its system. Sweetpotato genotypes accumulate viruses and the virus load is the major problem. Sweetpotato virus disease (SPVD) occurs after infection of two viruses: the sweetpotato feathery mottle virus (SPFMV) and the sweetpotato chlorotic stunt virus (SPCSV). These two viruses distort, stunted, cause chlorosis and narrowing of leaves leading to photosynthetic disturbance. SPCSV is the more problematic component of SPVD, because yield losses due to SPFMV -without SPCSV infection -are relatively low and SPFMV resistance of sweetpotato breaks down after the plant is infected by SPCSV. Of all the sweetpotato genotypes, the ones mostly affected by viruses are the orange fleshed sweetpotato genotypes.
Keywords: orange fleshed sweetpotato; virus disease; yield; SPVD and symptoms